Single-cell analysis of bovine muscle-derived cell types for cultured meat production - Messmer, Tobias; Dohmen, Richard G. J.; Schaeken, Lieke; Melzener, Lea; Hueber, Rui; Godec, Mary; Didoss, Carin; Post, Mark J.; Flack, Joshua E. (Frontiers in Nutrition, 2023)
Cultured meat technologies leverage the proliferation and differentiation of animal-derived stem cells ex vivo to produce edible tissues for human consumption in a sustainable fashion. However, skeletal muscle is a dynamic and highly complex tissue, involving the interplay of numerous mono-and multinucleated cells, including muscle fibres, satellite cells (SCs) and fibro-adipogenic progenitors (FAPs), and recreation of the tissue in vitro thus requires the characterisation and manipulation of a broad range of cell types. Here, we use a single-cell RNA sequencing approach to characterise cellular heterogeneity within bovine muscle and muscle-derived cell cultures over time. Using this data, we identify numerous distinct cell types, and develop robust protocols for the easy purification and proliferation of several of these populations. We note overgrowth of undesirable cell types within heterogeneous proliferative cultures as a barrier to efficient cultured meat production, and use transcriptomics to identify conditions that favour the growth of SCs in the context of serum-free medium. Combining RNA velocities computed in silico with timeresolved flow cytometric analysis, we characterise dynamic subpopulations and transitions between active, quiescent, and committed states of SCs, and demonstrate methods for modulation of these states during long-term proliferative cultures. This work provides an important reference for advancing our knowledge of bovine skeletal muscle biology, and its application in the development of cultured meat technologies.